Continuous Recursive Sliding Mode Control for Hypersonic Flight Vehicle with Extended Disturbance Observer. (29th November 2015) - Wu, Yunjie; Wang, Jianmin
Abstract : A continuous recursive sliding mode controller (CRSMC) with extended disturbance observer (EDO) is proposed for the longitudinal dynamics of a generic hypersonic flight vehicle (HFV) in the presence of multiple uncertainties under control constraints. Firstly, sliding mode tracking controller based on a set of novel recursive sliding mode manifolds is presented, in which the chattering problem is reduced. The CRSMC possesses the merits of both nonsingular terminal sliding mode controller (NTSMC) and high-order sliding mode controller (HOSMC). Then antiwindup controller is designed according to the input constraints, which adds a dynamic compensation factor in the CRSMC. For the external disturbance of system, an improved disturbance observer based on extended disturbance observer (EDO) is designed. The external disturbance is estimated by the disturbance observer and the estimated value is regarded as compensation in CRSMC for disturbance. The stability of the proposed scheme is analyzed by Lyapunov function theory. Finally, numerical simulation is conducted for cruise flight dynamics of HFV, where altitude is 110000 ft, velocity is 15060 ft/s, and Mach is 15. Simulation results show the validity of the proposed approach.